An iterated greedy algorithm for the no-wait flowshop scheduling problem to minimize makespan subject to total completion time. Issue 8 (3rd August 2021) - Nagano, Marcelo Seido; de Almeida, Fernando Siqueira; Miyata, Hugo Hissashi
Abstract : This article addresses the m -machine no-wait flowshop scheduling problem with the objective of minimizing makespan subject to an upper bound on total completion time. An iterated greedy-with-local-search algorithm is proposed and compared with a mathematical model and the best method found in the literature for solving this problem. Computational experiments and statistical analysis are conducted to evaluate the methods. The results show that the proposed approach offers fast and high quality solutions when compared with the mathematical model and at the same time outperforms the best existing algorithm in effectiveness and efficiency.